Phenotypic and molecular characterization of Pantoea stewartii causing bronzing disease in Malaysian jackfruit (Artocarpus heterophyllus) - Manaf, Norsyahidah (2017)
Jackfruit (Artocarpus heterophyllus) is one of the popular and the most widely grown fruit crop in Malaysia. Under the Third National Agricultural Policy, jackfruit has been recognized as having the potential to meet domestic demand, for export and as a replacement for imports. However, a disease known as fruit bronzing is frequently found infecting jackfruit. The disease is caused by Pantoea stewartii (P. stewartii), which is characterized by yellowish-orange to reddish discoloration of the affected pulps and rags in the fruit which can cause serious jackfruit losses. Once infected, the fruit quality is compromised and could discourage the consumers and processors. To date, no studies have been conducted on P. stewartii and fruit bronzing of jackfruit in Malaysia. The objectives of this study were; 1) to isolate and identify bacterial strains associated with bronzing disease in local jackfruit by using phenotypic characteristics and 2) to characterize genetic relationship of the bronzing-causing strains of jackfruit via molecular identification and phylogenetic analyses. In April 2016, symptoms of fruit bronzing in jackfruits were observed in Muadzam Shah jackfruit plantation of Pahang state. To identify the pathogen, 10 diseased fruits resembled bronzing symptom were collected from two fields prone to the disease, excised and cultured onto potato dextrose agar (PDA) medium and incubated overnight at 37 ºC. Four representative bacterial colonies were obtained and selected for further characterization. Bacterial colonies were round, yellow-pigmented, smooth and translucent. All strains were Gram-negative short rod-shaped, positive for Kovacs oxidase and catalase tests, and negative for potassium hydroxide (KOH) reaction. These are characteristics of Pantoea spp. For the pathogenicity test, 10 ml of 108 CFU/ml bacterial suspension of four selected strains were injected into healthy detached jackfruits of J33 (Tekam Yellow) variety. Fruits that were infiltrated with sterile distilled water served as a negative control. Inoculation with all strains were performed in three replications, as well as the uninoculated control detached fruits. The inoculated fruits produced bronzing symptoms as observed on naturally diseased samples, whereas control fruits remained asymptomatic. Strain cultures were re-isolated and showed the morphological and biochemical characteristics as previously described. The PCR amplification of 16S gene using 27F and 1492R primer set produced a 1400 bp amplicon in each strain. Sequencing analysis revealed that all strains were 99% identical to Pantoea stewartii reference strain M073 (Accession no. KJ742705). Species-specific PCR with primers ES16 and ESIG2c showed all strains displaying a 920 bp amplicon. The sequence data were deposited in GenBank (Accession nos. KY195916 to KY195919). Phylogenetic analyses of the ES16/ESIG2c gene sequences clustered all strains into Pantoea stewartii subspecies (subsp.) stewartii DC283 reference strain (Accession no. AJ311838), with 100% posterior probability. To our knowledge, this is the first report of bronzing disease caused by Pantoea stewartii subsp. stewartii in jackfruit in Malaysia.